2019
DOI: 10.1097/md.0000000000016421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy on the survival of cervical cancer patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 33 publications
0
50
0
1
Order By: Relevance
“…FIGO stage was classified by the 2009 FIGO stage system. And the continuous predictors (age and tumor size) were divided into subgroups by previously reported cutoff points [6,16]. The time calculated from diagnosis to dead or censored was defined as overall survival.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…FIGO stage was classified by the 2009 FIGO stage system. And the continuous predictors (age and tumor size) were divided into subgroups by previously reported cutoff points [6,16]. The time calculated from diagnosis to dead or censored was defined as overall survival.…”
Section: Patientsmentioning
confidence: 99%
“…Therefore, using FIGO stage system to estimate prognosis of cervical cancer is not entirely satisfactory. And many other factors have been identified related to the survival of cervical cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an increased external pelvic dose will probably not compensate for exclusion of brachytherapy treatment. Prior studies have also confirmed the advantage of combined external and intracavitary therapy compared with external therapy alone [8,16,17]. The total dose (D90) to the HRCTV (external plus intracavitary) was significantly higher in the group treated with needles.…”
Section: Vaginal Toxicity (Only Recorded In the Igabt-group)mentioning
confidence: 80%
“…Thus, an increased external pelvic dose (or boost dose) would probably not compensate for exclusion of brachytherapy treatment. Prior studies have also confirmed the advantage of combined external and intracavitary therapy compared with external therapy alone [9,14]. On the other hand, the size of HRCTV and the use of interstitial needles were neither statistically associated with tumor recurrences nor with cancer-specific survival rate in the complete series.…”
Section: Discussionmentioning
confidence: 95%